Research and Innovation in Society: Contextualizing a Society Touch in the Academic Block in Tanzania - Ngonzi, Tibuhinda; Jisaba, Andrew (International Journal of Educational Studies, 2019)
In the triad of academic and specialized research institutions, business, and society blocks, the academic and specialized research institutions domain is naturally expected to be the leader or the principal producers in research and innovation for development (R&I for D). The remaining business and society entities on the other hand are expected to be the target consumers of the products. For production to happen however, the producers need resources, incentives and motivations as factor inputs. The factors may originate in intra-domains for the respective domain’s own use of end results such as it is for business organizations, or across domains for mutual benefits. In turn, the origination of the motives and incentives play a role in defining the relevance of the R&I products such as the emergence of appropriate research for appropriate innovations. It is in the observations of this paper that overtime, R&I in Tanzania is becoming undermined by the decline in the cross dimensional flow, specifically the academic (universities) versus society flow. In fact, apart from the specialized institutions, the academics member of the producer block is increasingly becoming too specialized and servicing its own motives in comparison to addressing societal needs. In this paper, we theoretically challenge the phenomenon and use the functional perspectives of the Triple helix model (THM) of university-industry-government cooperation to suggest for innovative education in enhancement of cross border interactions between university and society.